Strong Ion and Weak Acid Analysis in Severe Preeclampsia: Potential Clinical Significance. Issue 1 (March 2017) - Ortner, C.M.; Combrinck, B.; Allie, S.; Story, D.; Landau, R.; Cain, K.; Dyer, R.A.
Abstract : ( Br J Anaesth. 2015;115:275–284) It has been suggested in preliminary work that abnormal acid-base status in pregnant women may be an indicator of preeclampsia disease severity. However, studies are scarce and there are no comprehensive analyses of independent or confounding factors. As acid/base measures using base excess (BE) have been used to predict outcomes in other clinical areas, the authors of the present study analyzed acid/base balance in women with severe preeclampsia and identified potential biological predictors of adverse outcomes.